Ubiquitin carboxyl-terminal hydrolase L-1 in brain: Focus on its oxidative/nitrosative modification and role in brains of subjects with Alzheimer disease and mild cognitive impairment - Butterfield, D. Allan (Free radical biology & medicine, 2021)
Neurons must remove aggregated, damaged proteins in order to survive. Among the ways of facilitating this protein quality control is the ubiquitin-proteasomal system (UPS). Aggregated, damaged proteins are targeted for destruction by the UPS by acquiring a polymer of ubiquitin residues that serves as a signal for transport to the UPS. However, before this protein degradation can occur, the polyubiquitin chain must be removed, one residue at a time, a reaction facilitated by the enzyme, ubiquitin C-terminal hydrolase (UCH-L1). In Alzheimer disease brain, this normally abundant protein is both of lower levels and oxidatively and nitrosatively modified than in control brain. This causes diminished function of the pleiotropic UCH-L1 enzyme with consequent pathological alterations in AD brain, and the author asserts the oxidative and nitrosative alterations of UCH-L1 are major contributors to mechanisms of neuronal death in this devastating dementing disorder and its earlier stage, mild cognitive impairment (MCI). This review paper outlines these findings in AD and MCI brain.